Miljöpåståenden i marknadsföring - Europeiska kommissionens direktivförslag om miljöpåståenden och dess påverkan på svensk rätt - Spang Dyhrberg Nielsen,Katrine (2024)
As a result of the ongoing climate challenges, interest in environmental and climate issues has increased across society. Consumers, businesses, and international organizations are all striving to contribute to the green transition. In particular, consumers are demanding sustainable products, prompting many businesses to use environmental claims in their marketing. However, such claims are often vague and misleading, exposing consumers to the risk of greenwashing. To address this issue, the European Commission has proposed a new directive on substantiation and communication of explicit environmental claims. The directive aims to reduce greenwashing and ensure that consumers can trust the information provided by businesses in their marketing. The directive includes detailed provisions on how environmental claims should be substantiated and presented, as well as rules governing the use of environmental labels. Additionally, the directive proposes that environmental claims be subject to prior verification by an accredited verifier before being used in marketing, along with strict sanctions for businesses that violate the provisions of the directive. The provisions in the proposed directive will have implications for Swedish law. Therefore, the purpose of this thesis is to examine how environmental claims in marketing are regulated under current Swedish law and to analyse how the proposed directive is expected to affect the Swedish legal framework. In Swedish law, environmental claims in marketing are regulated through the Marketing Act, case law, and self-regulation. Provisions addressing misleading marketing, comparative advertising, and good marketing practice are primarily invoked to address environmental claims in marketing. These provisions establish requirements for the use of environmental claims in marketing to ensure that they are not deemed unfair. In particular, there is a high standard of reliability. This means that an environmental claim must be used with a relative meaning, specifying what is intended by the claim, and must provide a fair overall impression. Further detailed requirements are set out in the ICC Advertising and Marketing Communications Code and in the European Commission’s guidance on the Unfair Commercial Practices Directive, which establish strict standards for the use of environmental claims in marketing. Although there is already comprehensive regulation of environmental claims in Swedish law, the proposed directive includes detailed provisions that are not currently regulated under existing law. The most significant changes to the Swedish legal framework are expected to concern environmental labeling, environmental labeling systems, the introduction of rules on prior verification and sanctions. In particular, the rules on prior verification could lead to significant changes for Swedish law, as they may potentially affect Swedish freedom of expression and conflict with the constitutionally protected prohibition against censorship.
Keywords: immaterialrätt; marknadsföringsrätt; miljöpåståenden; greenwashing; grönmålning